Depression in patients with inflammatory bowel disease is associated with increased risk of dementia and Parkinson’s disease: A nationwide, population-based study - Choi, Kookhwan; Lee, Hyun Jung; Han, Kyungdo; Koh, Seong-Joon; Im, Jong Pil; Kim, Joo Sung (Frontiers in Medicine, 2022)
Background: Inflammatory bowel disease (IBD) may be associated with depression which is considered an important cause of dementia and Parkinson’s disease (PD). In the present study, the effects of depression on the development of dementia and/or PD in patients with IBD were evaluated. Methods: A nationwide population-based cohort study was conducted using claims data from the Health Insurance Review and Assessment Service in Korea. The incidence of dementia and PD were analyzed based on the presence of depression in patients with IBD. Results: During a mean follow-up of 8 years, IBD patients with depression experienced dementia (6.7% vs. 2.0%; p < 0.001) and PD (1.1% vs. 0.3%; p < 0.001) significantly more than IBD patients without depression. Compared with IBD patients without depression, the risk of developing dementia was significantly higher in IBD patients with depression (adjusted hazard ratio (aHR) for IBD, Crohn’s disease (CD), and ulcerative colitis (UC), 2.03, p < 0.001; 1.68, p = 0.033; 2.13, p < 0.001, respectively). Compared with IBD patients without depression, the risk of developing PD was significantly higher in IBD patients with depression (aHR for IBD, CD, and UC, 2.54, p < 0.001; 1.93, p = 0.470; 2.75, p < 0.001, respectively). The cumulative incidence of dementia and PD in IBD patients with depression was significantly higher than in IBD patients without depression and showed a steady increase after a diagnosis of depression. Conclusions: The risk of dementia and/or PD increased after a diagnosis of depression in patients with IBD.